What happened to Lani Garver - Plum-Ucci, Carol, 1957- (Harcourt, 2004)
Sixteen-year-old Claire is unable to face her fears about a recurrence of her leukemia, her eating disorder, her need to fit in with the popular crowd on Hackett Island, and her mother's alcoholism until the enigmatic Lani Garver helps her get control of her life at the risk of his own. The close-knit residents of Hackett Island have never seen anyone quite like Lani Garver. Everything about this new kid is a mystery: Where does Lani come from? How old is Lani? And most disturbing of all, is Lani a boy or a girl? Popular Claire McKenzie isn't up to tormenting Lani with the rest of the high school elite. Instead, she decides to befriend the intriguing outcast. But within days of Lani's arrival, tragedy strikes, and Claire is left questioning herself, her friendships, and, most interesting of all, the possibility that angels may exist on earth.